DETERMINAN KEJADIAN STROKE DI RUANGAN RAWAT INAP RUMAH SAKIT TK II PUTRI HIJAU KESDAM I BB - Rukiani, Safitri; Nababan, Donal; Silitonga, Evawani M. (Akupun Tour Publisher, 2025)
According to WHO 2012, deaths from stroke of 51% worldwide are caused by high blood pressure. In addition, an estimated 16% of stroke deaths due to high blood glucose levels in the body. Stroke is broadly classified into ischemic and haemorrhagic strokes. Stroke risk factors include smoking, hypertension, hyperlipidemia, atrial fibrillation, ischemic heart disease, valvular heart disease, and diabetes (Goldszmith, 2009). This study aims to explain about the Determinant of Stroke Events in the Inpatient Room of TK II Putri Hijau Kesdan I Bukit Barisan Hospital. This type of research is a survey research using explanatory research or explanatory research. The population was all stroke patients in the Inpatient Room of TK II Putri Hijau Kesdam I Bukit Barisan Hospital as many as 136 patients, the sample size in this study was 43 patients. Data analysis using Chi-Square test of 95% confidence level (p <0.05) and multiple logistic regression test. The results show that age, sex, family history, smoking, nutritional status / obesity, hypertension, and diabetes have a relationship with stroke sufferers. The most influencing factors of stroke were history of hypertension (p = 0.028), physical activity (p = 0.032) and smoking habit (p = 0.035). The effect of history of hypertension, physical activity and smoking habit had an effect on 95.3% stroke patient (Overall Percentage), while the remaining 4.7% was influenced by other factors. The results of this study are expected to be useful in the handling of stroke patients, so as to reduce the morbidity and mortality of stroke patients and improve self-sufficiency of stroke patients and also regularly follow the process of therapy provided for optimal recovery process.